Enhanced Heat Transfer Efficiency through Formulation and Rheo-Thermal Analysis of Palm Oil-Based CNP/SiO2 Binary Nanofluid - Kulandaivel, Sridhar; Ngui, Wai Keng; Samykano, Mahendran; Reji Kumar, R.; Suraparaju, Subbarama Kousik; Sofiah, A. G. N.; Muhamad, Mat Noor (Wiley-Blackwell, 2024)
The present work addresses the shortcomings of heat transfer fluid behavior by emphasizing solutions for improved stability, enhanced thermal properties, and environmental sustainability. The study introduces an innovative hybrid nanofluid combining silicon dioxide (SiO2) and cellulose nanoparticles (CNP) into analytical-grade Palm oil, adopting a two-step methodology. This endeavor represents a significant advancement in exploring SiO2–CNP-Palm oil hybrid nanofluids, positioning them as promising candidates for advanced heat transfer media. Physical characterization analysis confirms the successful integration of SiO2 and CNP into analytical-grade Palm oil. The nanosuspensions of CNP-Palm oil, SiO2-Palm oil, and SiO2/CNP-Palm oil are prepared at varying volume concentrations. All nanosuspensions demonstrated good stability after ultrasonication, as evidenced by optical performance and sedimentation studies, which endure for up to 60 d. Fourier transform infrared (FT-IR) analysis further substantiates the chemical stability, revealing no emergence of peaks associated with the diffusion of nano-additives. The thermogravimetric analysis (TGA) also affirms superior thermal stability in all nanosuspensions compared to base fluids. Rheological studies indicate that Palm oil exhibits Newtonian behavior. The nanofluid containing 0.1 w/v% SiO2/CNP nanoparticles exhibits a significant enhancement in thermal conductivity, showcasing an impressive 81.11% improvement. In addition, the nanofluid demonstrates an increase in viscosity with higher nanoparticle concentrations and decreased viscosity with rising temperatures.